2018
DOI: 10.1186/s40168-018-0555-8
|View full text |Cite
|
Sign up to set email alerts
|

The gut of the finch: uniqueness of the gut microbiome of the Galápagos vampire finch

Abstract: BackgroundDarwin’s finches are a clade of 19 species of passerine birds native to the Galápagos Islands, whose biogeography, specialized beak morphologies, and dietary choices—ranging from seeds to blood—make them a classic example of adaptive radiation. While these iconic birds have been intensely studied, the composition of their gut microbiome and the factors influencing it, including host species, diet, and biogeography, has not yet been explored.ResultsWe characterized the microbial community associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
57
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 79 publications
12
57
2
1
Order By: Relevance
“…This finding is also supported by studies in other taxa including larval amphibians and aquatic invertebrates [71]. Previous studies found a more prominent role of host diet in shaping the gut microbiome [72,73], particularly within clades such as lizards [74], fish [32,67,75], birds [76,77], or mammals [78]. Captivity may produce bottom-up effects on microbiomes by altering environmental conditions and diets from field conditions [41].…”
Section: Discussionsupporting
confidence: 61%
“…This finding is also supported by studies in other taxa including larval amphibians and aquatic invertebrates [71]. Previous studies found a more prominent role of host diet in shaping the gut microbiome [72,73], particularly within clades such as lizards [74], fish [32,67,75], birds [76,77], or mammals [78]. Captivity may produce bottom-up effects on microbiomes by altering environmental conditions and diets from field conditions [41].…”
Section: Discussionsupporting
confidence: 61%
“…However, the only indication of this function that we detected was a higher abundance in vampire finches of ASV20, taxonomically identified as C. somerae (family Fusobacteriaceae, phylum Fusobacteria) (figure 3; electronic supplementary material, table S2). A separate sequence analysis of these vampire finch faecal samples confirmed this finding [39]. C. somerae is known to produce cobalamin (vitamin B12), a vitamin that has recently been found to serve important roles in the microbial metabolism of other essential compounds such as folate, ubiquinone and methionine [40].…”
Section: (A) Evidence For H1: No Convergencesupporting
confidence: 56%
“…5a). This pattern bears high resemblance to the microbiota composition of other neotropical birds [42]and also to that of Darwin's finch [43]. Proteobacteria and Firmicutes were the dominant phyla in the sunbirds treated with nicotine and anabasine after four weeks.…”
Section: The Effect Of Time On the Gut Microbiomesupporting
confidence: 53%